2020
DOI: 10.3390/cells9061336
|View full text |Cite
|
Sign up to set email alerts
|

The Network of Angiotensin Receptors in Breast Cancer

Abstract: The renin-angiotensin system (RAS) is a network of proteins regulating many aspects of human physiology, including cardiovascular, pulmonary, and immune system physiology. The RAS is a complicated network of G-protein coupled receptors (GPCRs) (i.e., AT1R, AT2R, MASR, and MRGD) orchestrating the effects of several hormones (i.e., angiotensin II, angiotensin (1–7), and alamandine) produced by protease-based transmembrane receptors (ACE1 and ACE2). Two signaling axes have been identified in the RAS endocrine sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…The AT1R is found to be overexpressed in various malignancies, including breast carcinoma cells, pancreatic adenocarcinoma cells, and hepatocarcinoma cells, as shown by in vitro studies [ 318 ]. In vivo also showed the overexpression of AT1R in ER-positive breast malignancies [ 319 ], glioblastomas [ 320 ], pancreatic ductal cancers [ 321 ], squamous cell carcinomas of the skin [ 322 ], and gastric cancers [ 323 ].…”
Section: Key Individual Gpcrs and Their Signaling Pathways Involved In Various Cancermentioning
confidence: 99%
“…The AT1R is found to be overexpressed in various malignancies, including breast carcinoma cells, pancreatic adenocarcinoma cells, and hepatocarcinoma cells, as shown by in vitro studies [ 318 ]. In vivo also showed the overexpression of AT1R in ER-positive breast malignancies [ 319 ], glioblastomas [ 320 ], pancreatic ductal cancers [ 321 ], squamous cell carcinomas of the skin [ 322 ], and gastric cancers [ 323 ].…”
Section: Key Individual Gpcrs and Their Signaling Pathways Involved In Various Cancermentioning
confidence: 99%
“…It is unclear at this time and in the future whether initiating therapy with angiotensin receptor blockers should be accompanied by screening testing to assess the individual risk of possible development of melanoma and breast cancer, for example. Two socially and health-significant diseases with increasing frequency, for which the role of the renin angiotensin system in the tumor tissue is already real or experimentally proven [1][2][3]. An additional aggravating factor when starting treatment with sartans is the (in) ability to detect up to 3 nitrosamines as contaminants in the manufacturing process, which in its turn, according to FDA / EMA data, are able to lead to an additional 11 cancers forms [6].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the renin angiotensin system in various other cancers such as breast cancer e.g. is discussed in the past, as this fact is still the subject of many discussions, which do not find (for reasons unknown at the moment and for all of us) still a definitive solution or change of approach before the introduction of systemic antihypertensive therapy with sartans [3,4]. In vivo data on metastatic melanomas, cutaneous melanomas and dysplastic nevi after therapy with sartans in the world literature are already dozens [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of activating the RAS pathway axis signaling has been mostly studied in tumor cells. On top of the usual blood pressure regulation role of ATR1, more recent observations showed that AT1R mediates several pathological events associated with activated RAS, such as upregulation of cell proliferation, inhibition of apoptosis, motility, migration, invasion, and angiogenesis (see Figure 3 ) [ 33 , 34 , 35 , 36 ]. In contrast, the Ang (1,7)-MAS receptor and the Ang II-AT2R pathways are thought to antagonize many of the cellular actions of the Ang II-AT1R axis.…”
Section: Part 1: Renin–angiotensin System Blockers and Malignanciesmentioning
confidence: 99%